Reviewing the Ruling of the Constitutional Court Number 90/PUU-XXI/2023 Concerning the Requirements for President and Vice President Candidates in the Perspective of Progressive Law - Wiradirja, Imas Rosidawati; Hadi Purnomo; Yulianto, Antonius Wantri; Tejo, Eko Susanto; Sari, Shinta Intan; Gunawan, Verawati; Muhamad Rivaldi, (International Journal of Scientific Research and Management (IJSRM), 2024)
Indonesia is both a legal state and a democratic state, characterized by sovereignty being in the hands of the people. One form of democracy is the election of the president and vice president who are directly elected by the people. Approaching the 2024 general election, there is a phenomenon that is really attracting the attention of the Indonesian people, namely regarding the judicial review of one of the requirements for presidential and vice presidential candidates as regulated in Article 169 letter q of the Election Law. In this article, the author will analyze whether the Constitutional Court has the authority to examine, decide and change the requirements for presidential and vice presidential candidates? Apart from that, what is the decision of the Constitutional Court’s number 90/PUU-XXI/2023 when viewed from a progressive legal perspective? This article uses a normative juridical method, namely by examining approaches to theories, concepts, and reviewing related laws and regulations. The results of the discussion concluded that the Constitutional Court had the authority to try this case. As a result, one of the requirements for a presidential or vice presidential candidate is to be “at least 40 years old or have/are currently holding positions elected through general elections, including regional elections”. From a progressive legal point of view, the decision of the Constitutional Court’s number 90/PUU-XXI/2023 is a form of rule breaking and social conditions also require that presidential candidates and/or vice presidential candidates do not have to be at least 40 years old, but must also pay attention to experience factors. Therefore, this is a new form of law and it must be useful for achieving justice, well-being and human happiness.